2020
DOI: 10.1111/his.14026
|View full text |Cite
|
Sign up to set email alerts
|

Should you repeat mismatch repair testing in cases of tumour recurrence? An evaluation of repeat mismatch repair testing by the use of immunohistochemistry in recurrent tumours of the gastrointestinal and gynaecological tracts

Abstract: Aims The role of mismatch repair (MMR) testing has evolved from identifying Lynch syndrome patients to predicting response to immune checkpoint inhibitors. This has led to requests from clinicians to retest recurrences of MMR‐proficient primary tumours in the hope that the recurrence may show a different MMR status and qualify the patient for treatment. We aimed to determine whether repeat testing is warranted. Methods and results We evaluated recurrent tumours (local recurrences or metastases) from 137 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Moreover, our findings show that MMR profiles are not fixed from primary to locally recurrent or metastatic CRC, with 10.6% of cases showing discordant MMR protein expression. While discordance of MMR profiles between primary CRC and corresponding metastatic or recurrent disease has been previously described, the frequency of discordance is incompletely understood, with estimates from 0% to 31% being reported [7,[24][25][26][27][28]. Importantly, both a loss and a gain of MMR expression from primary to recurrent or metastatic disease have been described, with one study reporting preserved MMR profiles in 18.8% of paired metastatic lesions with MMR protein-deficient primary tumours [25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, our findings show that MMR profiles are not fixed from primary to locally recurrent or metastatic CRC, with 10.6% of cases showing discordant MMR protein expression. While discordance of MMR profiles between primary CRC and corresponding metastatic or recurrent disease has been previously described, the frequency of discordance is incompletely understood, with estimates from 0% to 31% being reported [7,[24][25][26][27][28]. Importantly, both a loss and a gain of MMR expression from primary to recurrent or metastatic disease have been described, with one study reporting preserved MMR profiles in 18.8% of paired metastatic lesions with MMR protein-deficient primary tumours [25].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of neoadjuvant or adjuvant therapies on MLH1, PMS2 or MSH2 expression, however, is not well established and may be insignificant [14,30]. A paper by Aird et al reported that although 2% of primary and corresponding metastatic CRC cases displayed discordant MMR profiles, all could be explained by either MLH1 promoter hypermethylation or adjuvant radiotherapy [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations